Development of Electronic Modules Based on Socioscientific Issues on Biotechnology Material to Improve Argumentation Skills - Fitri Husni Mardiyah; Widi Purwianingsih; Rini Solihat; Anugrah Ayumaharani Widianingsih; Dita Astriningrum; Rani Siti Khoerunnisa (Universitas Negeri Semarang, 2025)
This study aims to develop an electronic module based on socio-scientific issues on biotechnology material using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. This module is designed to improve high school students' argumentation skills and perceptions of biotechnology. The subjects of the study consisted of 76 grade XI students in West Bandung Regency. The three-tier test instrument was used to identify student misconceptions, with the results showing the highest percentage of misconceptions in the concepts of STEM cells (22%), recombinant bacteria (21%), and cloning (19%). Needs analysis was carried out through data triangulation, including diagnostic tests, teacher interviews, and student questionnaires. The electronic module developed includes material features, practicums, socio-scientific issues, perception space, and evaluation. Validation by material experts, technology, teachers, and students produced an average score of 3.31 (valid criteria) with a feasibility percentage of 83%. Field trials on 20 students showed an average effectiveness score of 3.19 (80%), included in the very valid category. The results of the study indicate that this module is effective in improving student understanding, interesting to use, and feasible to be applied in distance learning. The implications of this study emphasize the importance of developing innovative learning media to overcome misconceptions and encourage scientific literacy based on contemporary issues.